Improved long-term survival with coronary artery bypass graft surgery compared to percutaneous coronary intervention in diabetics with multivessel disease. (25th November 2020) - Tam, D; Dharma, C; Rocha, R; Farkouh, M; Abdel-Qadir, H; Sun, L.Y; Gaudino, M; Wijeysundera, H.C; Austin, P.C; Udell, J; Fremes, S; Lee, D.S
Abstract: Background: While randomized clinical trials have demonstrated the superiority of coronary artery bypass grafting (CABG) over percutaneous coronary intervention (PCI) in patients with diabetes and multivessel coronary artery disease (CAD), there remains a paucity of observational evidence comparing these two modalities. Methods: Clinical and administrative databases for Canada's most populous province, Ontario, were linked to obtain records of all patients with angiographic evidence of multivessel CAD (defined as: 2-vessel and 3-vessel disease) treated with either isolated CABG or PCI from October 2008 to March 2017. Left main disease was excluded in the primary analysis. Baseline characteristics of patients undergoing CABG and PCI were compared and 1:1 propensity score matching was performed to account for baseline differences. 30-day mortality was compared in the matched groups. Late mortality and the composite of major cardiovascular and cerebrovascular events (MACCE, consisting of stroke, myocardial infarction (MI), repeat revascularization, and death) were compared between the matched groups using a stratified log rank test and Cox-proportional hazards model. The individual non-fatal components of MACCE were compared using the Fine-Gray model that accounted for death as a competing risk. A secondary analysis that included patients with left main disease was also performed for the outcome of late mortality. A sensitivity analysis that excluded patients with acute coronary syndrome was also conducted for late mortality. Results: A total of 9, 395 and 4, 016 patients underwent CABG and PCI respectively. Prior to matching, CABG patients were younger (65.7 vs 68.5 years, p<0.001), more likely male (78% vs 73%, p<0.001) and with more severe CAD. Propensity score matching based on 24 baseline covariates yielded 3, 782 well-balanced pairs. There was no difference in early mortality between CABG and PCI (2.3% vs 2.5%, p=0.65). The rate of all-cause mortality over 8-years was significantly higher with PCI compared to CABG (Figure- HR: 1.35, 95% CI: 1.23–1.50). The cumulative incidence of MI (HR 1.91, 95% CI: 1.66–2.20) and need for repeat revascularization (HR: 4.06, 95% CI: 3.54–4.66) were significantly higher with PCI over 8 years. There was no difference in late stroke between PCI and CABG (stroke (HR: 0.85, 95% CI: 0.68–1.07). Overall MACCE was higher in PCI compared to CABG (HR: 1.94, 95% CI: 1.80–2.09). In our secondary analysis that included patients with left main disease, findings were robust and late mortality remained higher with PCI compared to CABG (HR: 1.42, 95% CI: 1.30–1.54). In a sensitivity analysis where patients with acute coronary syndrome at the time of presentation were excluded, late mortality remained higher with PCI (HR: 1.30, 95% CI: 1.12–1.49) in 2, 028 matched pairs. Conclusions: In patients with multivessel CAD and diabetes we observed improved long-term mortality and freedom from MACCE at 8-years with CABG compared to PCI. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Canadian Institutes of Health Research